Wide-line NMR and DSC studies on intrinsically disordered p53 transactivation domain and its helically pre-structured segment - Tompa, Peter (BMB Rep, 2016)
Wide-line (1)H NMR intensity and differential scanning calorimetry measurements were carried out on the intrinsically disordered 73-residue full transactivation domain (TAD) of the p53 tumor suppressor protein and two peptides: one a wild type p53 TAD peptide with a helix pre-structuring property, and a mutant peptide with a disabled helix-forming propensity. Measurements were carried out in order to characterize their water and ion binding characteristics. By quantifying the number of hydrate water molecules, we provide a microscopic description for the interactions of water with a wild-type p53 TAD and two p53 TAD peptides. The results provide direct evidence that intrinsically disordered proteins (IDPs) and a less structured peptide not only have a higher hydration capacity than globular proteins, but are also able to bind a larger amount of charged solute ions. [BMB Reports 2016; 49(9): 497-501]